1993
DOI: 10.1139/v93-064
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of noncovalent interactions in the solid state. 3. X-ray crystal structures of [H4(cyclam)][FeCl5(OH2)](Cl)2 and [H4(cyclam)][CF3COO]4, two network hydrogen bonded solids

Abstract: . 71,433 (1993). On discute des implications des structures cristallines dans la perspective de la creation rationnelle de solides polaries.[Traduit par la redaction]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The Fe-Cl bond (2.333(2) Å) which is trans to the water molecule, is evidently shorter than other four Fe-Cl distances (their average is 2.385 Å), presumably as a manifestation of trans infl uence (Table 2). The angles in the anion are very close to the published data (Figgis 1978 ), some quite remarkable perturbations from the octahedron were observed (Subramanian 1993 , respectively clearly confi rm the presence of water molecule in the anion (Piszczek 2003). Other bands at 436 and 349 cm -1 confi rm the bond formation between iron and oxygen atoms.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The Fe-Cl bond (2.333(2) Å) which is trans to the water molecule, is evidently shorter than other four Fe-Cl distances (their average is 2.385 Å), presumably as a manifestation of trans infl uence (Table 2). The angles in the anion are very close to the published data (Figgis 1978 ), some quite remarkable perturbations from the octahedron were observed (Subramanian 1993 , respectively clearly confi rm the presence of water molecule in the anion (Piszczek 2003). Other bands at 436 and 349 cm -1 confi rm the bond formation between iron and oxygen atoms.…”
Section: Resultssupporting
confidence: 83%
“…These compounds have been easily prepared from aqueous solutions containing ACl or ABr and appropriate ferric halide, and in several cases also HX. Another compounds which contain [FeCl 5 (H 2 O] 2-anions and organic cations such as are H 4 (cyclam) 4+ , (enH 2 ) 2+ and (dienH 3 ) 3+ have been recently prepared and characterized (Subramanian 1993, James 2001. The crystals of (NH 4 ) 2 [FeCl 5 (H 2 O)] have been usually prepared by slow evaporation of aqueous solutions containing a (1-2):1 molar mix of NH 4 Cl and FeCl 3 ·6H 2 O (Sharma 1974, Figgis 1978, McElearney 1978, Partiti 1985.…”
Section: Introductionmentioning
confidence: 99%
“…However, no X-ray structural studies of the tetracation salts were reported until we began our studies. Unlike cyclam and its dication, [~, ( c~c l a m ) ]~+ , the tetracation, [~~( c~c l a m ) ]~+ , adapts an exodentate conformation in the structures of salts we reported previously (24,29) and in all six structures described herein. In other words, the nitrogen atoms are oriented away from the ring cavity, occupying positions as far away as possible from each other on the ring periphery (Scheme 1).…”
Section: Resultsmentioning
confidence: 60%
“…IR spectra were organometallics (ferrocene derivatives and acetylides) ( 17, recorded on a Perkin-Elmer 1600 series FTIR using solid state 18), and organic cation salts (7,(19)(20)(21)(22)(23)(24) (5) 4 (0.500 g, 0.783 mmol) was dissolved in 6 mL of water and to this 0.330 g (3.4 mmol) of KCNS in 6 mL of water was added. On standing in an ice bath, most of the KClO, precipitated and was removed by filtration.…”
Section: Methodsmentioning
confidence: 99%
“…The protonated amino groups are directed away from the macrocycle, being located as far away as possible from each other to minimize electrostatic interactions [16]. As a result of the tendency to adopt this conformation, the molecule can simultaneously hydrogen bond up to eight different hydrogen bond acceptors such as carboxylate or sulphate groups [16][17][18]. Additionally in the case of the cyclam tosylate salt, the tosyl moieties arrange themselves to form hydrophobic regions above and below the hydrogen-bonded sheet comprising the polar layer [18].…”
Section: Structural Investigation Of the Smectic Phasesmentioning
confidence: 99%